Combined application of biochar and PGPR consortia for sustainable production of wheat under semiarid conditions with a reduced dose of synthetic fertilizer - Ijaz, Muhammad (Braz J Microbiol, 2019)
This study investigates the combined effect of locally adopted plant growth promoting rhizobacteria (PGPR), biochar, and synthetic fertilizer on the wheat crop for the production and economic returns. A total of 20 PGPR strains were isolated from three different ecological zones of Pakistan and were evaluated. Of them, three isolates were selected for further studies. The treatments included (i) control with a full dose of the recommended fertilizer, (ii) control with half a dose of the fertilizer, (iii) PGPR consortia with half a dose of the fertilizer, (iv) biochar with half a dose of the fertilizer, and (v) PGPR + biochar with half a dose of the fertilizer. The study was repeated at three different locations. The data collected for leaf area index (LAI), grain yield, biological yield, straw yield, and harvest index (HI) revealed significant differences (P ≤ 0.05) for the locations and treatments, but the interaction of location and treatments was not significant. Based on the productivity and economic returns, the treatment with PGPR + biochar with half a dose of the fertilizer proved to be the best. Thus, the use of the PGPR consortia and biochar can improve the yield and profit of wheat crop with reduced synthetic fertilization. [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s42770-019-00043-z) contains supplementary material, which is available to authorized users.